How environmental policy synergy can enhance urban ecological resilience: insights from text mining analysis in China - Tao Ge; Zixuan Hao; Yuan Chen (Humanities & Social Sciences Communications)
Abstract Rapid urbanization has swelled a substantial influx of rural populations into urban areas, resulting in severe ecological risks. Based on environmental policies enacted in 285 Chinese cities from 2006 to 2022, this paper uses text mining analysis to quantify environmental policy synergy from the perspectives of policy actor synergy and policy instrument synergy and further investigates its impact on urban ecological resilience. The results show that environmental policy synergy significantly enhances urban ecological resilience. Policy actor synergy and policy instrument synergy respectively determine the direction and degree of environmental policy synergy affecting urban ecological resilience, and their joint enhancement generates a strong promoting effect. Heterogeneity analysis reveals that such effects are more pronounced in regions with strict environmental regulation intensity and high economic development levels. Furthermore, mechanism analysis demonstrates that factor agglomeration effects and green innovation effects serve as key channels through which environmental policy synergy enhances urban ecological resilience. The government should strengthen environmental policy synergy, tailor environmental policies to local conditions, and promote high-end factor agglomeration and innovation capacity.